A formação continuada na trajetória profissional de professores de Educação Física - Bernardi, Ana Paula (2008)
As we narrate our life story we have the possibility of reviewing and rethinking the construction process of our education as teachers, both in personal and professional terms. Taking as the starting point the oral narrative of three Physical Education teachers, we attempted to examine and understand how they perceive the process of continuing education in relation to their professional career. In order to do so, we adopted the qualitative research, the case study that focused in the continuing education process of teachers, and the oral narrative as the means to produce the necessary information for the analysis; these talks were taped and trancribed. The participants were three Physical Education teachers who had graduated from a specialization course and who had been in the teaching career for at least five years. To analyse the information, the following categories were created: a) teachers and their stories and teacher perception in relation to the course taken and b) continuing education. Beginning with the clarification of all categories of analysis, the discussion of the information took a tringular form between the talk of the participants, the literature and the author´s interventions. The experiences narrated by the teachers in relation to their career and continuing education are rather similar, but the manner in which each signified given moments of their educational process is different because they are unique stories, constructed on a plurality of experiences. The continuing education courses are usually courses of specialization, and are offered by professors in the graduate programs of Higher Education. Ther motivation to take these courses vary, but it is the locus where they can discuss and problematize their pedagogical praxis and other issues related to their teaching context. The specialization course in itself may be just a little grain of sand, but since we are the sum of our experiences, that is, of many grains of sand, during our life history, such courses may be considered a landmark, a decisive moment in their educational process, for there they allow themselves to look, think, review and reconstruct parts of their lifepath. Through their narratives I gathered that these teachers understood that these courses, in isolation, did not have the strength to transform them and their lifepath, but that they represent the culminating moment in which these students, mothers, sisters, wifes and intellectuals, gave meaning to the experiences they went through. The specialization course promotes this opening, this possibility to view the future with a more profound look, a more flexible thought in relation to their own teaching.